(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2013)
Clonal multiplication of Aegle marmelos was achieved through in vitro culture. Cotyledonary nodes from one month old in-vitro grown seedlings of Aegle marmelos were cultured on MS medium supplemented with BAP, Kn, and IBA either alone or in combination. The highest regenerative response was observed on medium containing 2.5 mg/L BAP and 0.5 mg/L Kn from node and shoot tip within 8-10 days. When regenerated shoots were subcultured on MS medium supplemented with 0.2 mg/L BAP and 0.02 mg/L Kn, maximum number of multiple shoots were observed after third phase of subculture. Poor response was found using MS medium supplemented with Kn only. In vitro induced shoots were transferred into root induction medium consisting of half-strength MS supplemented with auxins, IAA, IBA or NAA. Rooting was best in medium supplemented with 1.0 mg/L IBA. Rooted plantlets were acclimatized and transferred to the soil with 96% survival rate. DOI: http://dx.doi.org/10.3329/bjsir.v48i1.15408 Bangladesh J. Sci. Ind. Res. 48(1), 13-18, 2013